PENGARUH MOTIVASI TERHADAP PRESTASI KERJA KARYAWAN PADA PT. PLN UP3 PAREPARE - Paesal, Andi Adriani (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
The purpose of this study aims to determine the effect of motivation on employee performance at PT. PLN UP3 Parepare. The location of this research was carried out at PT. PLN UP3 Parepare Jl. Veterans, while the time of the study began in January to March 2020, the data analysis technique used was this analysis using simple linear regression because it only consisted of 2 variables, namely motivation and work performance. Simple linear regression aims to determine the direction of the relationship between the independent variable and the dependent variable whether positive or negative and to predict the value of the dependent variable if the value of the independent variable increases or decreases. From the results of research on the influence of motivation on employee performance at PT PLN PERSERO Parepare Branch, it can be concluded as follows: From the results of research that has been carried out using simple linear regression analysis, it is known that the t-count value is 5.953 while the significant value in the research results is 0.00 less than 0.05, it is known that the motivation variable has a significant effect on employee performance at PT PLN PERSERO Parepare Branch. Based on the results of research and discussion that have been stated previously, the suggestions that can be given are: The results in this study are motivation greatly affects the work performance of PT PLN PERSERO employees Ca Parepare and the motivation given is good, however, there is still a need to increase incentives/bonuses for employees who work overtime outside of working hours; For the leadership of PT PLN PERSERO Parepare Branch to be even better in providing encouragement and motivation to its employees as with the company's mission and vision so that in the future employee performance can increase, and the company's strategic goals can be achieved Keywords: Motivation and Achievement.